Lateral load bearing characteristics of light gauge steel and lightweight concrete shear walls - Chunri Quan; Qiang Huang; Dongbin Li; Yong Chen (Acta Polytechnica CTU Proceedings)
In China, there is a new structural system named light gauge steel and lightweight concrete (LSLC) structure, which used lightweight concrete as structural material in composite way with cold-formed steel. Here, the shear walls are the main structural members for the LSLC structure, which are assembled with the light gauge steel lattice columns and horizontal braces, and filled with lightweight concrete. In this study, the LSLC shear walls are experimentally investigated to evaluate their failure mechanism and lateral load bearing capacity. For this purpose, several specimens with different shear span ratio are designed and tested under static cyclic loading. This paper presents the damage state and hysteresis loops of the specimens detailly. Then, the lateral load bearing characteristics of the LSLC shear walls are discussed according to the failure mechanism, such as shear and flexural failure. Finally, the calculation methods of lateral strength for the LSLC shear walls are proposed based on the diagonal strut mechanism and sectional force equilibrium.